PENGARUH KEAMANAN, KEMUDAHAN, DAN DISKON DOMPET DIGITAL TERHADAP PERILAKU KONSUMTIF MAHASISWA PASCASARJANA IAIN PALOPO - Ginanjar, Muh. Ginanjar; Muh. Rasbi; Fasiha; Atika Tahir; Linda A. Ali (Moneta: Jurnal Manajemen & Keuangan Syariah, 2024)
The aim of this research is to determine the impact of digital wallets on consumer behavior of IAIN Palopo graduate students. The population of this research is all IAIN Palopo postgraduate students totaling 340 people who use digital wallets with a sample selected of 78 respondents. This research method uses quantitative methods with multiple linear regression tests. The findings of this research indicate that security influences the constective behavior of IAIN Palopo Postgraduate Students with a significant value of 0.004. Convenience has no effect on the constative behavior variable of IAIN Palopo Postgraduate Students with a significant value of 0.976, while digital wallet discounts have no effect on the constitive behavior variable of IAIN Palopo Postgraduate Students with a significant value of 0.317. And security, convenience and discounts related to digital wallets simultaneously influence the purchasing behavior of postgraduate students at IAIN Palopo with a significant value of 0.000